Analisis Pengaruh Timeliness, Apology, Redress, Facilitation, Credibility Dan Attentiveness Terhadap Kepuasan Pelanggan (Studi Kasus Bpjs Kesehatan Di Kabupaten Batang) - Tri Handayani; Muliawan Hamdani; Setyo Pantawis (FEB Universitas Sultan Ageng Tirtayasa, 2019)
Today the need for health is in need for all people, health has become a basic necessity, everyone will try to do various things so that his health can be guaranteed, Health is a human right and one of the elements of welfare that must be realized in accordance with the ideals the ideals of the Indonesian nation. Health is a fundamental right of every individual and all citizens are entitled to health care. Therefore, it is necessary to manage the health control in terms of cost and quality. This study aims to examine whether timeliness, apology, redress, facilitation, credibility, and attentiveness affect customer satisfaction. The number of samples in this study were 125 respondents with Acidental sampling technique. This research uses multiple linear regression analysis technique. The result of data analysis shows that timeliness, apology, facilitation, credibility, and attentiveness have positive effect on customer satisfaction while redress variable has no significant effect on customer satisfaction. Based on the determinant coefficient test (R2) in the known Adjusted R2 of 0.745 it shows that the dependent variable of customer satisfaction can be explained by independent variables consisting of timeliness, apology, redress, facilitation, credibility and attentiveness of 75% while the remaining 25% by other factors outside the model.